Pengaruh Literasi Keuangan, Financial Technology, Orientasi Kewirausahaan dan Inovasi Produk terhadap Kinerja Keuangan UMKM Kecamatan Banjarsari Kota Surakarta - Annisa Riyu Mezaluna; Edi Wibowo (Jurnal Manajemen Riset Inovasi, 2024)
The development of culinary MSMEs in Banjarsari District, Surakarta City has developed rapidly, but the increase in the number of culinary MSMEs in Banjarsari District, Surakarta City is not necessarily followed by an increase in the financial performance of these MSMEs This study aims to find out and analyze the influence of financial literacy, financial technology, entrepreneurial orientation, and innovation towards the financial performance of culinary MSMEs in Banjarsari District, Surakarta City. Data collection in this study uses a questionnaire distributed to respondents. The sample in this study amounted to 95 culinary MSMEs in Banjarsari District, Surakarta City with the type of sampling, namely purposive sampling with the consideration that the MSMEs have been running for at least 2 (two) years. The analysis methods used in this study are descriptive analysis, multiple linear regression analysis, t-test, F test (model accuracy test), and determination coefficient test (R2). The results showed that the determination coefficient (adjusted R Square) is 0.548. Means This means that the amount of contribution of the influence of the independent variable X1 (financial literacy), X2 (financial technology), X3 (entrepreneurial orientation) and X4 (product innovation) towards Y (performance finance) by 54.8%. The rest (100% - 54.8%) = 45.2% is influenced by other variables outside the model such as the work environment, company size, market competitiveness, operational costs, working capital, etc.